The architecture of art history : a historiography - Crinson, Mark; Williams, Richard J., 1967- (History of art and architecture, 2019)
Many disciplines have a stake in the history of architecture? sociology, anthropology, human geography, to name a few. This book deals with perhaps the most influential tradition of all? art history? examining how the relation between the disciplines of art history and architectural history has waxed and waned over the last one hundred and fifty years.0In this study, Mark Crinson and Richard J. Williams point to a decline in the importance attributed to the role of architecture in art history over the last century - which has happened without crisis or self-reflection. The book explores the problem in relation to key art historical approaches, from formalism, to feminism, to the social history of art, and in key institutions from the Museum of Modern Art, to the journal October. Among the key thinkers explored are Banham, Baxandall, Giedion, Panofsky, Pevsner, Pollock, Riegl, Rowe, Steinberg, Wittkower and Woelfflin. The book will provoke debate on the historiography and present state of the discipline of art history, and it makes a powerful case for the reconsideration of architecture.